Examining the effect of non-specialised clinical rotations upon medical students' Thanatophobia and Self-efficacy in Palliative Care: a prospective observational study in two medical schools - Gryschek, Guilherme; Cecilio-Fernandes, Dario; Moreira de Barros, Guilherme Antonio [UNESP]; Mason, Stephen; Carvalho-Filho, Marco Antonio de (Bmj Publishing Group, 2020)
Introduction Including palliative care (PC) in overloaded medical curricula is a challenge, especially where there is a lack of PC specialists. We hypothesised that non-specialised rotations could provide meaningful PC learning when there are enough clinical experiences, with adequate feedback. Objective Observe the effects of including PC topics in non-specialised placements for undergraduate medical students in two different medical schools. Design Observational prospective study. Setting Medical schools in Brazil. Participants 134 sixth-year medical students of two medical schools. Methods This was a longitudinal study that observed the development of Self-efficacy in Palliative Care (SEPC) and Thanatophobia (TS) in sixth-year medical students in different non-specialised clinical rotations in two Brazilian medical schools (MS1 and MS2). We enrolled 78 students in MS1 during the Emergency and Critical Care rotation and 56 students in MS2 during the rotation in Anaesthesiology. Both schools provide PC discussions with different learning environment and approaches. Primary outcomes SEPC and TS Scales were used to assess students at the beginning and the end of the rotations. Results In both schools' students had an increase in SEPC and a decrease in TS scores. Conclusion Non-specialised rotations that consider PC competencies as core aspects of being a doctor can be effective to develop SEPC and decrease TS levels.
Keywords: medical education & training; palliative care; adult palliative care